Perancangan Sistem Inventory Berbasis Dekstop - Muhammad Farhan Ramadhan; Rangga Cahya Gumilang; Sayyid Zakki Galbi; Wasis Haryono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Recording in and out of goods and stock data of goods is very important in the work of a store because it can slow down work. Using computers in business today has become a necessity for every businessman because it can reduce errors and work performance. So in the business world it is very important. At this time, at the Pusaka Rama rice shop, they are doing a manual recap of goods data, so the author makes a desktop-based inventory system application using the Java programming language, MYSQL database and the method is waterfall.